Longitudinal study on blood and biochemical indexes of Tibetan and Han in high altitude area - Yuan, ZhiMin; Zou, YuanWu; Liu, XiaoXing; Wang, LongHao; Chen, Cheng (Frontiers in Public Health, 2023)
Objective This study aims to review the blood routine and biochemical indicators of the plateau population for three consecutive years, and analyze the impact of the plateau on these blood indicators of the Tibetan population and the Han immigrant population. Method These parameters were extracted from the Laboratory Department of Ali District People’s Hospital in Tibet from January 2019 to December 2021, including blood routine, liver and kidney function, blood lipids, myocardial enzyme spectrum, and rheumatic factor indicators. Changes in these parameters were analyzed over 3 consecutive years according to inclusion and exclusion criteria. Result A total of 114 Tibetans and 93 Hans participated in the study. These parameters were significantly different between Tibetan and Han populations. Red blood cells (RBC), hemoglobin (HGB), hematocrit (HCT), mean hemoglobin content (MCH), mean corpuscular hemoglobin concentration (MCHC), white blood cells (WBC), lymphocytes (LYMPH) and monocytes (MONO) were significantly higher in Hans than Tibetans (p < 0.05). Biochemically, total bilirubin (TBIL), direct bilirubin (DBIL), albumin (ALB), urea nitrogen (Urea), creatinine (Cr), uric acid (UA), glucose (GLU), triglycerides (TG) and creatine kinase isoenzyme (CKMB) were significantly higher in Hans than Tibetans; aspartate aminotransferase (AST), glutamyl transpeptidase (GGT), alkaline phosphatase (ALP), antistreptolysin (ASO), and C-reactive protein (CRP) were significantly higher in Tibetans than Hans (p < 0.05). There were no obvious continuous upward or downward trend of the parameters for 3 consecutive years. Conclusion In high-altitude areas, Han immigrants have long-term stress changes compared with Tibetans. The main differences are reflected in the blood system, liver and kidney functions, etc., which provide basic data for further research on the health status of plateau populations.